Self-Organization for Collective Action: An Experimental Study of Voting on Sanction Regimes. (29th October 2013) - Markussen, Thomas; Putterman, Louis; Tyran, Jean-Robert
Abstract: Entrusting the power to punish to a central authority is a hallmark of civilization, yet informal or horizontal sanctions have attracted more attention of late. We study experimentally a collective action dilemma and test whether subjects choose a formal sanction scheme that costs less than the surplus it makes possible, as predicted by standard economic theory, or instead opt for the use of informal sanctions (IS) or no sanctions. Our subjects choose, and succeed in using, IS surprisingly often, their voting decisions being responsive to the cost of formal sanctions. Adoption by voting enhances the efficiency of both IS and non-deterrent formal sanctions. Results are qualitatively confirmed under several permutations of the experimental design.